2016
DOI: 10.1111/geb.12532
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multimodal species abundance distributions is linked to spatial and taxonomic breadth

Abstract: Aim Species abundance distributions (SADs) are a synthetic measure of biodiversity and community structure. Although typically described by unimodal logseries or lognormal distributions, empirical SADs can also exhibit multiple modes. However, we do not know how prevalent multimodality is, nor do we have an understanding of the factors leading to this pattern. Here we quantify the prevalence of multimodality in SADs across a wide range of taxa, habitats and spatial extents. Location Global. Methods We used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 36 publications
3
43
1
Order By: Relevance
“…However, recent work has indicated that a small proportion of empirical SADs are, in fact, multimodal (e.g. Antão, Connolly, Magurran, Soares, & Dornelas, ; Dornelas & Connolly, ; Matthews & Whittaker, ; Vergnon, van Nes, & Scheffer, ). For example, a recent synthesis of 117 datasets found significant evidence of multimodality in c .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, recent work has indicated that a small proportion of empirical SADs are, in fact, multimodal (e.g. Antão, Connolly, Magurran, Soares, & Dornelas, ; Dornelas & Connolly, ; Matthews & Whittaker, ; Vergnon, van Nes, & Scheffer, ). For example, a recent synthesis of 117 datasets found significant evidence of multimodality in c .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent synthesis of 117 datasets found significant evidence of multimodality in c . 20% of cases (Antão et al, ). A number of potential causes of multimodality in SADs have been put forward, such as the amalgamation of different types of species within a single sample (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One is inclined to think so if there is a 'universal law'. Review [2] is steeped with the idea of a relatively simple equation for SADs, but it presents the opposite too, that different communities have rather different SADs and that groups of species within a community have different SADs, making the community's SAD a mixed one [5]. The SAD is mostly treated as a histogram, based on the binning of data into frequency classes (for a probability mass or density function).…”
Section: Introductionmentioning
confidence: 99%